3(6z-1)-4(z+2)=5(z+1)

Simple and best practice solution for 3(6z-1)-4(z+2)=5(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6z-1)-4(z+2)=5(z+1) equation:


Simplifying
3(6z + -1) + -4(z + 2) = 5(z + 1)

Reorder the terms:
3(-1 + 6z) + -4(z + 2) = 5(z + 1)
(-1 * 3 + 6z * 3) + -4(z + 2) = 5(z + 1)
(-3 + 18z) + -4(z + 2) = 5(z + 1)

Reorder the terms:
-3 + 18z + -4(2 + z) = 5(z + 1)
-3 + 18z + (2 * -4 + z * -4) = 5(z + 1)
-3 + 18z + (-8 + -4z) = 5(z + 1)

Reorder the terms:
-3 + -8 + 18z + -4z = 5(z + 1)

Combine like terms: -3 + -8 = -11
-11 + 18z + -4z = 5(z + 1)

Combine like terms: 18z + -4z = 14z
-11 + 14z = 5(z + 1)

Reorder the terms:
-11 + 14z = 5(1 + z)
-11 + 14z = (1 * 5 + z * 5)
-11 + 14z = (5 + 5z)

Solving
-11 + 14z = 5 + 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
-11 + 14z + -5z = 5 + 5z + -5z

Combine like terms: 14z + -5z = 9z
-11 + 9z = 5 + 5z + -5z

Combine like terms: 5z + -5z = 0
-11 + 9z = 5 + 0
-11 + 9z = 5

Add '11' to each side of the equation.
-11 + 11 + 9z = 5 + 11

Combine like terms: -11 + 11 = 0
0 + 9z = 5 + 11
9z = 5 + 11

Combine like terms: 5 + 11 = 16
9z = 16

Divide each side by '9'.
z = 1.777777778

Simplifying
z = 1.777777778

See similar equations:

| 4d+3=8 | | 7x+4x=12 | | -9x-1=71 | | 7x+4+=12 | | 217-5x=40x+22 | | 10-7x=127-28x | | 10-7x=127-18x | | 114-5x=2x+26 | | -8x-5=19 | | 5x^2+3x=3 | | 5y-2x=10 | | 0.04(x-0.2)=-0.03(2x+0.6) | | .167x^2-.333x-1=0 | | 9x+5=2x+33 | | 25-x^2= | | 8x-2x+18=0 | | (1+7i)+(9-1)=0 | | 0.3(c+5)=0.4(1-2c) | | r^2+5=0 | | r^2+1=0 | | x/(x-3)+3=5x/(3-x) | | 2(x-0.2)=3x-1.4 | | 3R+5-R= | | 10x^2-30x=0 | | (2x-1)+(x-11)+x+40=360 | | 4x+19=26-3x+8x | | 2x+4-20x=10 | | -3m+12=-48 | | 9+3x=39-12x | | 3x+5=1-x | | -2=-2(k+19) | | -2y=11-x |

Equations solver categories